Efficiency analysis of oral health resource allocation in public medical institutions in Yunnan Province at the end of the 13th five-year plan in China - Qi Sun; Jingjun Tian; Wenlin Lu; Jun Zhang; Zhangcheng Yin; Lan Yao; Xinchun Zou; Baofan Li; Yanhong Li; Juan Liu (BMC Oral Health)
Abstract Background This study aimed to analyze the efficiency of oral health resource allocation in public medical institutions in Yunnan Province at the end of the 13th Five-Year Plan period in China. The findings will provide a theoretical basis for the government and health administration departments to formulate regional medical and health plans and adjust policies and systems. Additionally, tailored recommendations will be proposed to optimize the allocation of oral health resources in public medical institutions in Yunnan Province and enhance resource utilization efficiency. Methods The present investigation scrutinizes the prevailing distribution of oral health resources within public institutions situated in Yunnan Province, marking the culmination of the 13th Five-Year Plan era. Employing cross-sectional analysis, the study utilizes conventional BCC and CCR models of Data Envelopment Analysis (DEA), alongside the super-efficiency SBM model, to assess the efficacy of resource allocation across 16 prefectures (or cities) within the province. Results In the conventional model analysis, the average technical efficiency (TE) of oral health resource allocation in 16 prefectures (or cities) of Yunnan Province at the end of the 13th Five-Year Plan was 0.867, with an average pure technical efficiency (PTE) of 0.914 and an average scale efficiency (SE) of 0.950. Out of the 16 decision-making entities, 2 exhibit effectiveness according to DEA standards, 2 demonstrate weak effectiveness, while 9 manifest ineffectiveness. In the SBM super-efficiency model analysis, the TE of the whole province was 0.820, accompanied by an average PTE of 1.110 and an average SE of 0.863. Five prefectures (or cities) attained super-efficiency effectiveness, with Kunming City (the provincial capital of Yunnan) distinguishing itself notably owing to substantial disparities in PTE (3.840) and SE (0.293). Conclusion On the whole, the efficacy in leveraging oral health resources within public medical institutions throughout Yunnan Province was deemed relatively commendable. Nonetheless, notable disparities among prefectures (or cities) persisted, characterized by an excessive concentration of premium resources. Ineffective resource utilization coexisted with inadequate distribution. It is recommended to customize the distribution of oral health resources in each area according to local conditions, facilitate the decentralization of premium resources, and enhance the capacity of oral medical services.